Breastfeeding challenges and opportunities during COVID‐19 in Hong Kong. (6th April 2023) - Hui, Lai Ling; Yeung, Karene HT; Chow, Ka Ming; Poon, Liona C; Ip, Patricia LS; Nelson, E Anthony S
Abstract : Barriers to sustain breastfeeding could be time and place specific. Here, we summarise new and old challenges to breastfeeding during COVID‐19 pandemic in Hong Kong, some of which were obtained from qualitative in‐depth interviews with health‐care professionals. We document how unnecessary massive mother–baby separations in hospitals and doubts in COVID‐19 vaccine safety seriously harm breastfeeding. We also discuss how the trends and increase in acceptance of receiving post‐natal care from family doctors, online‐antenatal class, work‐from‐home policy and telemedicine implicate new strategies to protect, promote and support breastfeeding during and after the pandemic. The challenges from the COVID‐19 pandemic on breastfeeding have revealed new opportunities to support breastfeeding in Hong Kong and similar settings where exclusive breastfeeding for 6 months is still not the norm.